Peran Bank Sampah sebagai Lembaga Berbasis Masyarakat dalam Pengelolaan Sampah - Bunga Dwima Sarry; Sasmito Jati Utama (Public Administration Dept, Faculty of Social and Political Science, 2023)
Services in the waste sector have been regulated through Law Number 18 of 2008 concerning waste management and Minister of Environment and Forestry Regulation 14 of 2021 has regulated community involvement or participation in the Waste Bank institution. This research examines how Community Participation in Waste Management Through Garbage Banks along with supporting and inhibiting factors for community participation in RW 02 Medokan Semampir, Surabaya City. The method used in this research is a qualitative method with a descriptive approach. The focus of this study discusses participation in decision making, participation in implementation, participation in benefits and participation in participation in evaluation. Data collection techniques in this study used observation, interviews and documentation. This is similar to the facts on the ground which show maturity in community-based waste management carried out by residents so that waste management activities through collection, sorting, weighing, recording and recycling processes are carried out in an innovative, creative, consistent and collective manner that can contribute economically and environmentally for the local community. Factors that encourage community participation in community-based waste management in RW 02 Medokan Semampir are the existence of administrators, support from officials and availability of forums. Meanwhile, the factor that inhibits community participation in waste management in RW 02 Medokan Semampir is the legality of the waste bank structure.